Age pattern of sexual activities with the most recent partner among men who have sex with men in Melbourne, Australia: a cross-sectional study. Issue 3 (31st August 2020) - Kilner, Alex; Fairley, Christopher K; Burrell, Sam; Bradshaw, Catriona S; Chen, Marcus Y; Chow, Eric P F
Abstract : Background: Sexual behavioural studies among men who have sex with men (MSM) are predominantly focused on penile-anal intercourse. Other non-anal sexual activities are under-studied. This study aimed to examine the age pattern of a range of sexual activities among MSM with the most recent male sex partner. Methods: We conducted a survey among MSM attending the Melbourne Sexual Health Centre in 2017. This survey asked about nine different sexual activities with their most recent regular and casual partner. A Chi-square trend test was used to examine the age patterns of each sexual activity. Results: A total of 1596 men answered the survey and their median age was 30 (IQR 25–37) years. With casual partners, kissing was the most common activity (92.4%), followed by performing penile-oral sex (86.0%) and receiving penile-oral sex (83.9%). The least common activity was insertive rimming (38.1%). Young men were more likely to engage in kissing (ptrend <0.001), receptive rimming (ptrend =0.004) and receptive penile-anal sex (ptrend <0.001) but they were less likely to have insertive penile-anal sex compared with older MSM. With regular partners, the most common activity was kissing (97.4%), followed by touching penises (90.0%) and performing penile-oral sex (88.3%). Age was not associated with most types of sexual activity with regular partners except mutual masturbation and receptive penile-anal sex. Younger men were more likely to masturbate mutually (ptrend =0.028) and engage in receptive penile-anal sex (ptrend =0.011). Conclusions: The pattern of sexual activities shows age-related differences with casual partners but less so with regular partners in MSM.